2018
DOI: 10.3390/nu10070835
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Dietary One-Carbon Metabolism-Related B Vitamins and the Risk of Esophageal Cancer: A Dose-Response Meta-Analysis

Abstract: Several B vitamins are essential in the one-carbon metabolism pathway, which is central to DNA methylation, synthesis, and repair. Moreover, an imbalance in this pathway has been linked to certain types of cancers. Here, we performed a meta-analysis in order to investigate the relationship between the intake of four dietary one-carbon metabolism-related B vitamins (B2, B6, folate, and B12) and the risk of esophageal cancer (EC). We searched PubMed, Web of Science, and Embase for relevant studies published thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Deficiencies of some certain micronutrients, such as folate and vitamin B 6 which are the key methyl donor and cofactor for the enzyme serine hydroxymethyltransferase respectively, have been recognized as the risk factors for cancers including ESCC [7, 8]. Folate and other B vitamins like B 2 , B 6 and B 12 play important roles in the one-carbon metabolism pathway, which is associated with DNA methylation, synthesis and impaired DNA repair [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiencies of some certain micronutrients, such as folate and vitamin B 6 which are the key methyl donor and cofactor for the enzyme serine hydroxymethyltransferase respectively, have been recognized as the risk factors for cancers including ESCC [7, 8]. Folate and other B vitamins like B 2 , B 6 and B 12 play important roles in the one-carbon metabolism pathway, which is associated with DNA methylation, synthesis and impaired DNA repair [9].…”
Section: Introductionmentioning
confidence: 99%
“…These cycles require sufficient concentrations of vitamin B 2 and B 12 as cofactors for the enzymes MTHFR and methionine synthase, otherwise folate will become trapped as 5,10-methylenetetrahydrofolate or 5-methyltetrahydrofolate and the generation of methionine will be negatively impacted [11]. However, the association between vitamin B 2 intake and EC risk is not yet entirely understood, and the conclusion has been inconsistent [7]. Several studies illustrated that high intake or plasma concentration of vitamin B 12 were associated with increased risk of cancers including EC [7, 1214], but the mechanism remains unclear and epidemiological studies have always showed inconsistent findings [8, 15].…”
Section: Introductionmentioning
confidence: 99%
“…When the lowest category was open-ended, the lower boundary was set to zero. When the highest category was open-ended, we assumed the length of the open-ended interval to be the same as that of the adjacent interval [40,41,42,43,44,45,46,47]. Heterogeneity between studies was evaluated using I 2 (i.e., the proportion of total variation explained by variation between studies).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the intake of these vitamins may induce DNA methylation and gene expression changes and modify the risk of diseases where DNA methylation play an important role such as cancer. In support of this notion, increased intake of vitamins B2, B6, and B12 by humans have been shown to inversely correlate with cancers such as esophageal cancer [146], cervical intraepithelial neoplasia [76], colorectal cancer [104], and prostate cancer [105]. However, the association between vitamin B levels or administration and DNA methylation was only reported in a few studies that measured the joint effect of vitamin B and folic acid status or included vitamin B in a combined model of other vitamins and micronutrients.…”
Section: Micronutrients and Dna Methylation And Their Impact On Camentioning
confidence: 99%